Isabella Bird’s Unbeaten Tracks in Japan ou le récit de voyage comme autoportrait d’une aventurière engagée - Floriane REVIRON-PIÉGAY (E-REA)
Unbeaten Tracks in Japan is much more than just Isabella Bird’s account of her discovery of Japan; it is also the story of a woman who wanted to break free from the constraints imposed upon her at home by a stifling, patriarchal society. Bird chose to explore unbeaten tracks both literally speaking and figuratively speaking as her travel account plays with the conventions of the genre. The epistolary form of her narrative proved an ideal medium to engage her readers’ attention, sustained throughout the book by the author’s pledge to deliver novelty and adventure. Although committed to describing the “real Japan”, Bird sometimes gives in to the temptation to romanticize and most often it is her own self she fictionalizes. The narrative does not just narrate her encounter with the Other (either the Japanese people or the Aino people), it is also a kind of autofiction whereby Bird ponders over her role as a woman, as an adventurer and as a writer. The initial pretext of the expedition gives way to an ethnographic account of Bird’s encounter with the Aino people, native to the Northern Island of Yezo and oppressed by the Japanese forces. The text hovers between two different kinds of rhetoric, that of identification and similarity and that of differentiation and difference.